OPTIMALIZATION OF FEED DOSAGE AND FREQUENCY IN PRODUCTION OF ROTIFER (Brachionus rotundiformis) - Rina P. Astuti; Sophia L. Sagala; Gunawan Gunawan; Gede S. Sumiarsa; Philip T. Imanto (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
The availability of rotifer as live food is importance in a larval mariculture. Therefore a continuous and high production of rotifer is needed. The study was aimed to determine the frequency and dosage of the best food in rotifer culture. Nannochloropsis oculata, yeast and scott’s emulsion are used as potential feeds for rotifer. Three dosages of N. oculata (150,000; 250,000, and 350,000 cells/ind.rotifer/day) were applied in the study and were given twice per day. Meanwhile, yeast(0.5 g/106 ind./day) and Scott’s emulsion with different dosages (2, 4, and 8 μg/106 ind./day) were given with two different feeding frequencies (two and four times a day) for each dosages. Each treatment was done in triplicates. Sampling of rotifer was conducted in the morning (AM) and afternoon (PM). Water quality (temperature, dissolved oxygen and ammonia) was also measured. Growth and productivity of rotifer were determined from the number of rotifer and the number of rotifer eggs, respectively. The results showed that the optimum productivity of rotifer was achieved by giving N. occulata of 250,000 sel/ind/day, twice a day in four days culture. Meanwhile, treatment with yeast and Scott’s emulsion gave best performance when applying 0.5 g/106 and 2 μg/106 ind./day twice per day, respectively. Yeast and scott’s emulsion treatment yielded optimum production in two days of culture.Keywords: rotifer, productivity, yeast, Scott’s emulsion, foodd dosage